Foundations and Schools of Governing Politics - Al-Gharawi, Esraa Qassim Ghanim (Journal of Posthumanism, 2025)
The importance of this research lies in the intellectual foundations and schools of American foreign policy. It is necessary to analyze the political behavior of any state in terms of its intellectual structure. Political action does not arise from an intellectual vacuum, regardless of whether it is internal or external, its features are only shaped according to intellectual data, means that the political behavior of any state is, in reality, a reflection of the content of its intellectual structure. It seeks to translate this knowledge into reality within the framework of its dealings with others. The process of formulating American foreign policy relies primarily on official and unofficial institutions. This study necessitated that we approach the subject according to both the intellectual foundations and schools of thought that drive American foreign policy.